Peningkatan Pemahaman ‘Islamic Leadership’ untuk Pemuda Sumatera Utara - Muhammad Kaulan Karima; Ramadhani Ramadhani; Toni Nasution (Universitas Islam Negeri Sumatera Utara, 2021)
ABSTRACT. The case for youth moral decadentism at this time is veryconcerning, plus the condition of the nation is being deteriorated economically.The morality of the younger generation is certainly very worried, because theyare the ones who will be the leaders of the nation in the future. In Islam,leadership is one of the important elements, because the enforcement of justice isimpossible to achieve except with power/authority. Therefore, this devotion aimsto realize a strong, optimistic, intelligent, and religious young Islamic leader